Faktor determinan pembiayaan musyarakah dengan NPF sebagai variabel moderasi - Ela Lutfatus Syu’la; Sulistyo Sulistyo; Mochamad Fariz Irianto (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
This study aims to analyze the influence of DPK, CAR, and ROA on musyarakah financing with NPF as a moderation variable in Islamic commercial banks in Indonesia. Using a quantitative research approach, the data collection technique uses the documentation of the quarterly financial statements of Islamic commercial banks on the OJK website. The population of this study are Islamic commercial banks registered with the OJK for the 2017-2019 period. The results showed that NPF was not able to strengthen the influence of TPF and ROA on musyarakah financing, but was able to strengthen the effect of CAR on musyarakah financing. Limitations in this study only tested 3 independent variables, namely TPF, CAR and ROA. Further researchers are expected to be able to add other independent variables, including the variable Financing to Deposit Ratio (FDR) and Operational Cost of Operating Income (BOPO).